2018
DOI: 10.1055/s-0038-1636519
|View full text |Cite
|
Sign up to set email alerts
|

Pelvic Congestion Syndrome: Systematic Review of Treatment Success

Abstract: Pelvic venous insufficiency is now a well-characterized etiology of pelvic congestion syndrome (PCS). The prevalence of CPP is 15% in females aged 18 to 50 years in the United States and up to 43.4% worldwide. In addition to individual physical, emotional, and quality-of-life implications of CPP, there are profound healthcare and socioeconomic expenses with estimated annual direct and indirect costs in the United States in excess of 39 billion dollars. PCS consists of clinical symptoms with concomitant anatomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(34 citation statements)
references
References 50 publications
2
30
0
2
Order By: Relevance
“…Regarding the technical aspects, some authors suggest that the release of coils should begin at the lower aspect of the ovarian vein, trying to avoid the occlusion of the deep pelvic plexus; stainless steel or fibered platinum coils of several sizes (4-20 mm) can be used (Figure 5) [76]. In expert hands, a technical success of 100% has been reported, and a recent systematic review reports that partial or total clinical improvement (evaluated with VAS score at follow-up) following coils embolization ranges from 82.1% to 100% [77]. The main complications are represented by migration of the coils (described in 1.9% of cases) followed by coil misplacement, vein perforation, local phlebitis, and recanalization because of coil erosion; most adverse events are early, and no significant complications have been reported on prolonged follow-up [76].…”
Section: Clinical Results In Pelvic Congestion Syndromementioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the technical aspects, some authors suggest that the release of coils should begin at the lower aspect of the ovarian vein, trying to avoid the occlusion of the deep pelvic plexus; stainless steel or fibered platinum coils of several sizes (4-20 mm) can be used (Figure 5) [76]. In expert hands, a technical success of 100% has been reported, and a recent systematic review reports that partial or total clinical improvement (evaluated with VAS score at follow-up) following coils embolization ranges from 82.1% to 100% [77]. The main complications are represented by migration of the coils (described in 1.9% of cases) followed by coil misplacement, vein perforation, local phlebitis, and recanalization because of coil erosion; most adverse events are early, and no significant complications have been reported on prolonged follow-up [76].…”
Section: Clinical Results In Pelvic Congestion Syndromementioning
confidence: 99%
“…The target vein and the catheter should be prefilled with iodinated contrast and later the foam should be slowly injected, replacing the contrast in the target vessel in order to ensure the perfect vessel coverage and reduce the reflux. Studies reported in the literature have always used gelfoam in combination with other embolizing agents (coils, glues), and therefore it is not possible to comment on the efficacy of gelfoam as the only embolizing agent in the treatment of PCS [77,79].…”
Section: Clinical Results In Pelvic Congestion Syndromementioning
confidence: 99%
“…Pelvic venous insufficiency (PVI) is a very common hemodynamic phenomenon (estimated to be present in 20–43% of the population in women) [ 1 , 2 , 3 ], most often resulting from the reversal of venous blood flow, which occurs in the mechanism of outflow disorders, or excessive dilatation of the main venous axes (VAX) located within the abdomen and pelvis. The abovementioned pathophysiological phenomenon results in overloading of the capacitive venous vessels in the pelvis, most often the para-uterine and peri-vaginal venous plexuses ( Figure 1 ), thus generating so-called venous leaks from the pelvis and vulvo-perineal varicosities.…”
Section: Introductionmentioning
confidence: 99%
“…According to recent studies and the presented data, approximately 25-35% patients may reveal various anatomical abnormalities with a "collateral effect" in their abdominal or pelvic veins; however, the majority of cases result from pregnancy-induced overload and subsequent impairment of left ovarian and iliac veins axes [44][45][46][47]. Noteworthy, both anatomical variants and/or pregnancy-induced PVI may be the origin of perineal reflux, which, depending on the direction of its propagation, may result in the development of "atypical" varicose veins (usually located in lateral or posterior aspects of the thigh) or which, via the branches of the posterior accessory the saphenous vein (PASV), may contribute to the overload and subsequent insufficiency of the GSV.…”
Section: Discussionmentioning
confidence: 75%